Toward a Rational Architectural Practice: The Particular Case of Giorgio Grassi - De Paola, Pasquale (ARCC Conference Repository, 2013)
This paper provides an historical examination of Giorgio Grassi’s singular methodologica lapproach to architecture, which is primarily based on a self-questioning rigorous framework that reflects onthe autonomous nature of architectural production. From an operative point of view, Grassi’s work has been characterized by an uninterrupted methodological continuity that sought coherence and rigor as ultimate form of expression. In Grassi’s view, architecture is defined as a rational discipline that prioritizes reason above form in order to avoid a return to rhetorical formalist models of architectural production. In order to underline this intelligible rational methodology, my paper will attempt to deconstruct Grassi’spractice by elucidating his ideological association with the Italian Tendenza, and by critically breaking downhis most compelling work, La Costruzione Logica Dell’ Architettura. This system of inquiry will underline particular methodological components such as the reductive qualities of typological classification, the logicaland autonomous foundations of architecture, and, consequently the recognition of its rules and limits. Accordingly, those cyclical constituents will be historically and critically exposed to emphasize those methodological characteristics that advocate the establishment of an architectural discourse, which isideologically based on the idea of pure rationality. In Grassi’s case, the originating premises of rational epistemology - and the ultimate search for knowledge -propose a newfound interest in everything that can be logically classified. Rationalist principles indeed address cognitive issues related to the historical zeitgeist of architecture that privilege reason above experience, logic above instinct, and idea above form. Thus, according to Grassi, architecture should never be understood either aesthetically or morally, but it should be conceived as the only answer to real problems. Eventually, Grassi’s desire to establish a theory based on the triumph of reason over the image emerges as the most definitive methodological model of architectural production.